2019
DOI: 10.1002/chem.201901494
|View full text |Cite
|
Sign up to set email alerts
|

Sequence and Structure of Peptoid Oligomers Can Tune the Photoluminescence of an Embedded Ruthenium Dye

Abstract: The understanding of structure–function relationships within synthetic biomimetic systems is a fundamental challenge in chemistry. Herein we report the direct correlation between the structure of short peptoid ligands—N‐substituted glycine oligomers incorporating 2,2′‐bipyridine groups—varied in their monomer sequence, and the photoluminescence of RuII centers coordinated by these ligands. Based on circular dichroism and fluorescence spectroscopy we demonstrate that while helical peptoids do not affect the flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…There are many reasons for this, ranging from their ease of synthesis with unique side chain diversity 1 to their conformational versatility which opens up a wide range of potential applications relevant to biomaterial science 23 , therapeutics development, 45 and catalysis. 7,8,9 Peptoids should be regarded as biotic foldamers since their backbone closely resembles that of peptides with the side chains attached to the amide nitrogen atoms rather than the C carbons, and also because single-chain peptoids may exhibit biopolymer-like conformational behaviours.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There are many reasons for this, ranging from their ease of synthesis with unique side chain diversity 1 to their conformational versatility which opens up a wide range of potential applications relevant to biomaterial science 23 , therapeutics development, 45 and catalysis. 7,8,9 Peptoids should be regarded as biotic foldamers since their backbone closely resembles that of peptides with the side chains attached to the amide nitrogen atoms rather than the C carbons, and also because single-chain peptoids may exhibit biopolymer-like conformational behaviours.…”
Section: Introductionmentioning
confidence: 99%
“…33 (S)-N-(1-phenylethyl)glycine monomers are, for example, commonly used to induce right-handed helices. 9,34,35 Sequence requirements and chain length effects were carefully studied which established the rules for the formation and stabilisation of chiral PPI-type helical secondary structures from aromatic-containing monomers. 36,37,38 In contrast, the control of peptoid helicity from non-aromatic monomers has been much less investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Exploring this idea in the context of peptoids, Maayan has shown that suitably designed sequences bearing 2,2′‐bipyridine moieties can fold and associate in the presence of metal ions including Ru 2+ [39] . Chiral induction from the peptoid chain to the metal center was observed, and later work demonstrated alterations in the peptoid sequence could be used to tune photoluminescent properties of the complex [40] . Related bipyridine‐functionalized peptoids were shown to form complexes with other metals, including Cu 2+ , Co 2+ , and Ni 2+ [41] …”
Section: Peptoidsmentioning
confidence: 99%
“…[39] Chiral induction from the peptoid chain to the metal center was observed, and later work demonstrated alterations in the peptoid sequence could be used to tune photoluminescent properties of the complex. [40] Related bipyridine-functionalized peptoids were shown to form complexes with other metals, including Cu 2 + , Co 2 + , and Ni 2 + . [41] While most metalloproteins involve a single metal ion at each binding site, multimetallic clusters are found in some systems.…”
Section: Peptoidsmentioning
confidence: 99%
“…A number of oligomers with well‐defined spatial arrangements of functional groups have been designed and employed to coordinate to metals, and detection of the foldamer‐metal binding has been evaluated by monitoring changes to fluorescence features. In an excellent example, the Maayan laboratory detailed the importance of peptoid structural features to modulate the luminescence of bound Ru(II) in acetonitrile [49] . Coordinating 2,2’‐bipyridine groups were incorporated into peptoids with helical ( 16 ) or flexible structures.…”
Section: Fluorescent Supramolecular Receptors From Foldamersmentioning
confidence: 99%